A Framework for Document Delivery Services in an Open Distance e-Learning Environment Library. Issue 1 (14th March 2020) - Maluleke, Simon; Ngoepe, Mpho; Marutha, Ngoako Solomon
Abstract: Document delivery service in an open distance environment is one way of taking library services to remote students. However, this service is not without challenges. For example, problems related to document delivery services may include unclaimed library materials by students, which costs the library money, and 'return to sender' parcels from the post office. The purpose of this qualitative study was to investigate the provision of document delivery services in an ODeL environment with reference to the University of South Africa (UNISA). Data were collected through document analysis and interviews with purposively UNISA library staff working at the document delivery section. The findings indicated that UNISA library uses mail, courier and e-learning platforms for the provision of document delivery services. It was established that often, courier companies deliver parcels without contacting the students, which sometimes results in the parcel being received by the wrong recipient or returned to the university. It is concluded that even with the use of modern technology in document delivery services at UNISA, delivered documents still get lost. A framework for implementation of document delivery services that can speed up delivery and minimize loss of materials is suggested.